Persepsi dan Tantangan Siswa Pada Penggunaan Flipped Learning - Ardin, Hardiani; Mulyani, Sri; Yusuf, Nurwahida; ,, Hendriawan (Universitas Islam Negeri Alauddin Makassar, 2023)
Online learning during pandemic has been affecting many education aspects, in which both the teacher and students cannot run their learning process well. However, there are some approaches that may be implemented in educational institutions to solve those problems, one of them is flipped learning. Hence, this study focused on the students’ perceptions and their challenges on the use of flipped learning in their English classroom. This research was qualitative by applying case study design which involved 16 students from 7th semester at English Education Department of Institut Parahikma Indonesia, Gowa. The data were collected by using qualitative questionnaire and in-depth interview which were analyzed by using thematic analysis. The results of this research indicated that there were two categories of students’ perceptions on the use flipped learning approach, they are positive and negative perceptions. Positive perceptions included effective approach, engaging approach, efficient approach, improving students’ ICT skill, and new learning approach, while negative perceptions consisted of the students are lack of experience, time consuming, incomprehensible contents, and students feel tedious. Furthermore, the challenges faced by the students on the use of flipped learning approach are the network and media issue, the lack of interaction and the students’ discipline. Apart of the findings, this study can contribute and has valuable insights for the development of learning approach especially in online based learning, it can also make practical contributions for teachers and educators to design blended learning by considering this study's findings.